Szkolnictwo baletowe w Polsce i na ziemiach polskich – zarys dziejów - Sadowska , Katarzyna (Studia Edukacyjne, 2024)
The study aims to outline the history of ballet education in Poland and on Polish lands based on the method of analysis and criticism of literature within the qualitative research paradigm. Research on the research problem expressed in the question: “What is the outline of the history of ballet education in Poland?” belongs to the qualitative research paradigm. The topic of the history of ballet education in Poland can be considered important because although ballet has been present in Polish culture since the 16th century, in the Polish publishing market there are still relatively few studies on artistic education in the field of dance, or they are outdated. To gradually change this situation, the study’s authors reflected on the key events in the history of Poland in shaping the tradition of professional education in the profession of dancers, expressing the hope that this reflection will contribute to a broader discussion and an inspiration for further research analyses.